What happens in your day to day life at work? The role of daily hassles and uplifts between optimism and subjective well-being - Junça Silva, A.; Caetano, António; Lopes, M. (28th International Congress of Applied Psychology, 2014)
Introduction Research on positive affect in organizations supports that: daily work-related events are relevant factors to several daily outcomes at work. However, there is a lack of research exploring the role of specific humor daily events within work settings. As such, our aim is to explore the role of work-related daily events, conceived as daily hassles and daily uplifts, between optimism and employees´ well-being. Objectives Building on Affective Events Theory, we hypothesize that: 1) daily hassles will affect negatively employees´ subjective well-being, and; 2) daily uplifts will contribute positively to employees´ subjective well-being. Plus, and based on the literature review on optimism and subjective well-being, we hypothesize that: 3) daily uplifts will mediate the relationship between optimism and employees´ subjective well-being; and; 4a) the inverse relationship between daily uplifts and subjective well-being will be weaker in the presence of few daily hassles than many ones; 4b) daily hassles will moderate the positive and indirect effect of optimism on subjective well-being (through daily uplifts). Specifically, daily uplifts will mediate the indirect effect in the presence of many daily hassles but not in the presence of few daily hassles. Method To test these hypothesis, full-time employees from a call-center (N=380) were interviewed to describe work-related daily events experienced on that working day. Plus, they filled in a questionnaire with measures on optimism and subjective well-being. Results Results supported all the hypotheses. However results evidenced that daily hassles had a stronger contribution for individuals’ subjective well-being than daily uplifts. Furthermore, we found evidence for the mediation role of daily uplifts on the relationship between optimism and subjective well-being. In addition, daily hassles moderated the relationship between daily uplifts and employees’ subjective well-being. Further, the ratio of daily events and subjective well-being were positively and significantly correlated. Implications These findings suggest that the occurrence of daily uplifts might be a significant uplift for the well-being of optimistic employees. On the other hand, work-related daily hassles seem to be a powerful situational factor that threats individuals´ subjective well-being. Moreover, daily hassles seem to have a stronger impact on individuals’ well-being when compared to daily uplifts. In addition, it seems that daily uplifts explain the positive association of optimism and well-being. Plus, one found that the higher number of daily hassles at work, the higher effect of daily uplifts on optimistic employees’ subjective well-being. Overall, these results suggest that training employees within optimistic strategies as well as promote conditions for the occurrence of daily uplifts might play an important role on a working day. Further, employers and employees can feel better by enhancing the frequency of positive daily humor events and decreasing the frequency of daily hassles. Originality/Value The present study is one of the few studies that scrutinize the role of micro daily events within a working day and its relevance for employees´ sense of well-being. Plus, it is the first to explore the mediating role of those situational factors on the relationship between optimism and subjective well-being.